Respuesta :
Answer:
Smaller number = 13
Larger = 67
Step-by-step explanation:
(13 x 5) + 2 = 67 + 13 = 80
So let’s start by turning this into an equation
We know that the sum of the two numbers equals 80, so we’ll put it as s (smaller) + l (larger) = 80
We know that l is 2 more than 5 times s
s x 5 + 2 = l
Now if we go through some numbers to replace s with, we can make an equation by finding a number that fits the equation, in this case s would equal 13
s + ((s x 5) + 2) = 80
13 + ((13 x 5) + 2) = 80
13 + (65 + 2) = 80
13 + 67 = 80
So our smaller number would equal 13
And our larger number would equal 67
Hope this helped! I find that it’s a lot of trial and error with this method but it’s very simple :)
We know that the sum of the two numbers equals 80, so we’ll put it as s (smaller) + l (larger) = 80
We know that l is 2 more than 5 times s
s x 5 + 2 = l
Now if we go through some numbers to replace s with, we can make an equation by finding a number that fits the equation, in this case s would equal 13
s + ((s x 5) + 2) = 80
13 + ((13 x 5) + 2) = 80
13 + (65 + 2) = 80
13 + 67 = 80
So our smaller number would equal 13
And our larger number would equal 67
Hope this helped! I find that it’s a lot of trial and error with this method but it’s very simple :)